A proposal for the cutoff points of waist circumference values predictive of increased risk of Type 2 diabetes and hypertension in Arab adults - Aljohani, Naji; Ahmad, Mohamad; Alfaqeeh, Ashwaq; Bahnassi, Ahmed; Alhamdan, Nasser (Journal of Diabetes and Endocrine Practice, 2021)
Introduction: Central obesity is an established risk factor for diabetes mellitus (DM) and hypertension. We aimed to identify people at the highest risk by ethnically adjusted waist circumference (WC) cutoff points. Subjects and Methods: Data were collected from a cross-sectional study of 4350 Saudi adults aged 15–64 years using a stratified, multistage, cluster random sampling. DM was based on known history or fasting blood glucose higher than 7.0 mmol/L, and hypertension was determined by having a systolic blood pressure ≥140 mmHg and/or diastolic ≥90 mmHg. WC was measured midway between the lower costal margin and iliac crest during the end-expiratory phase. Results: The mean age for all the study population was 36.6 + 13.0 years (35.6 ± 12.0 years for females; 37.5 ± 13.9 years for males). The mean WC was 95.2 + 14.01 cm for males and 89.9 + 12.6 cm for females (P < 0.001). The prevalence of diabetes was 23.8% for all subjects. The prevalence of hypertension for all subjects was 25.5%. Receiver operator characteristics curves revealed that WC cutoff points for diabetes risk are 91 cm and 97 cm for women and men, respectively, and for hypertension are 90 cm and 97 cm for women and men, respectively. Conclusions: The present study proposes the obtained cutoffs to identify those at high risk for diabetes and hypertension in the Saudi population who can be considered candidates for preventive interventions.
Keywords: Anthropometrics; diabetes; hypertension; Saudi Arabia; waist circumference